Resveratrol Administration Ameliorates Hepatotoxicity in Mercuric Chloride-‎Induced Liver Injury in Rats - A Dawood, Rusul; Alghetaa, Hasan Falah; K Aladhami, Ahmed (The Iraqi Journal of Veterinary Medicine, 2023)
Mercuric chloride (HgCl2) pollution and poisoning has been a worldwide health ‎concern for decades, especially after the industrial revolutions. The aim of this study ‎was to investigate the role of resveratrol in reversing the deleterious effects of ‎HgCl2 exposure to resume the normal functions of hepatocyte. To achieve the study, ‎mature Sprague Dawley rats were assigned to five groups. Negative control group ‎‎(C) kept without any treatment; vehicle-treated group (D) received dimethyl ‎sulfoxide (DMSO); resveratrol-treated group (R), received 100 mg/kg of resveratrol; ‎HgCl2-intoxicated group (HD), received i.p. injection of HgCl2 at a dose of 1 mg/kg ‎for 30 consecutive days along to oral gavage of DMSO; and finally HgCl2-‎intoxicated group treated with resveratrol (HR) as same treatment strategy of R-‎group. At the endpoint of the experiment, blood samples were collected for ‎biochemical liver function tests along with serum concentrations of ‎malondialdehyde (MDA), glutathione (GSH), body weight, as well as ‎histopathological investigation was done too. Study results revealed a significant ‎‎(P<0.05) elevation in serum AST, ALP, GGT, and MDA in HD group in comparison ‎with HR group. However, resveratrol treatment has led to a significant (P<0.05) ‎increase in serum levels of GSH in HR group in comparison with the HD group. ‎Histopathological sections showed vacuolar degeneration in HD hepatocytes while ‎resveratrol treatment protected the hepatocytes against the chemical injury. ‎Altogether, It is concluded that resveratrol administration has the ability to increase ‎the resistance of liver against the HgCl2-induced hepatotoxicity via increase the ‎antioxidant yields such as GSH resulted in reduction of hepatocellular texture ‎damage.